$f(x)=\dfrac {1} {2}\left( \pi -x\right)$

Using the Fourier sine series expansion how to show following formula? (Range:$\left[ 0,\pi \right]$)

$$\sum\limits _{k=1}^{\infty }\dfrac {\left( -1\right) ^{k-1}} {2k-1}=\dfrac {\pi } {4}$$

up vote 2 down vote accepted

To obtain the Fourier sine series expansion for $f(x)$ the coefficients $a_n$ must vanish (see below). So let $g(x)$ be the odd function extending $f(x)$ to the interval $[-\pi,0[$ defined by

\begin{equation*} g(x)=\left\{ \begin{array}{l} \phantom{-}f(x)&=\phantom{-}\dfrac{\pi -x}{2},\qquad \phantom{-}0\leq x\leq \pi \\ \\ -f(-x)&=\color{blue}{-\dfrac{\pi +x}{2}}\qquad -\pi \leq x<0 \end{array} \right. \end{equation*}

whose graph in $[\pi,\pi]$ is shown in the following figure

enter image description here

$$g(x)=f(x)=\frac{\pi -x}{2}, x\in[0,\pi[ ; \; g(x)=-f(-x)=\color{blue}{-\frac{\pi +x}{2}},x\in[-\pi,0] $$

We know that the trigonometric Fourier series expansion for $g(x)$ in the interval $\left[ -\pi ,\pi \right] $ is given by

\begin{equation*} \frac{a_{0}}{2}+\sum_{n=1}^{\infty }\left( a_{n}\cos (nx)+b_{n}\sin (nx)\right) , \end{equation*} where the coefficients are the integrals \begin{eqnarray*} a_{n} &=&\frac{1}{\pi }\int_{-\pi }^{\pi }g(x)\cos (nx)\,dx\qquad n=0,1,2,\ldots , \\ b_{n} &=&\frac{1}{\pi }\int_{-\pi }^{\pi }g(x)\sin (nx)\,dx\qquad n=1,2,3,\ldots . \end{eqnarray*} The integrand $g(x)\cos (nx)$ is an odd function, while $g(x)\sin (nx)$ is even. So $a_{n}=0$ and

\begin{equation*} b_{n}=\frac{2}{\pi }\int_{0}^{\pi }g(x)\sin (nx)\,dx=\frac{2}{\pi } \int_{0}^{\pi }\frac{\pi -x}{2}\sin (nx)\,dx. \end{equation*} Evaluating this last integral we obtain $b_{n}=\frac{1}{n}$, which proves that \begin{equation*} f(x)=\frac{\pi -x}{2}=\sum_{n=1}^{\infty }\frac{1}{n}\sin (nx),\qquad 0\leq x\leq \pi , \end{equation*} (the Fourier sine series for the function $f(x)$ in the interval $\left[ 0,\pi \right] $). We see that $f(\pi/2)=\pi/4$. We just need to confirm that for $x=\pi /2$ this last series reduces to your series. Indeed since \begin{equation*} \sin \big(\frac{n\pi }{2}\big)=\left\{ \begin{array}{l} 1,\qquad n=1,5,\ldots ,4k+1,\ldots \\ 0,\qquad n=2,4,\ldots ,2k+2,\ldots \quad (k=0,1,2,\ldots)\\ -1,\quad \;n=3,5,\ldots ,4k+3,\ldots, \end{array} \right. \end{equation*} we have \begin{equation*} \frac{\pi }{4}=\sum_{n=1}^{\infty }\frac{1}{n}\sin \big(\frac{n\pi }{2}\big)=1-\frac{1 }{3}+\frac{1}{5}-\frac{1}{7}+\ldots = \sum\limits _{k=1}^{\infty }\dfrac {\left( -1\right) ^{k-1}} {2k-1} . \end{equation*}

Remark. For a Fourier cosine series we would need to extend $f(x)$ to an even function instead, because then $b_n$ would vanish.

We have that $$ \sum_{n\geq 1}\frac{\sin(nx)}{n} $$ is the Fourier sine series of a function that equals $\frac{\pi-x}{2}$ over the interval $(0,\pi)$.
If we evaluate such a series at $x=\frac{\pi}{2}$ we get that: $$ \sum_{n\geq 1}\frac{\sin\left(\frac{\pi n}{2}\right)}{n}=\color{red}{\sum_{k\geq 1}\frac{(-1)^{k-1}}{2k-1}} = \frac{\pi-\frac{\pi}{2}}{2} = \color{red}{\frac{\pi}{4}} $$ as wanted. An alternative approach is to notice that $$ \sum_{k=1}^{N}\frac{(-1)^{k-1}}{2k-1}=\sum_{k=1}^{N}(-1)^{k-1}\int_{0}^{1}x^{2k-2}\,dx = \color{blue}{\int_{0}^{1}\frac{dx}{1+x^2}}-(-1)^N\color{purple}{\int_{0}^{1}\frac{x^{2N}\,dx}{1+x^2}}$$ where the blue term equals $\color{blue}{\frac{\pi}{4}}$ and the purple term is $\color{purple}{O\left(\frac{1}{N}\right)}$.

Your Answer

 

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.